Handbook of Green Chemistry 2010
DOI: 10.1002/9783527628698.hgc008
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation for CC Bond Formation

Abstract: The formation of chemical bonds between carbon atoms is of fundamental significance. A major goal in the emerging field of green chemistry involves the design of by-product-free chemical processes, especially CÀC bond-forming processes applicable to renewable feedstocks [1]. This objective is aligned with longstanding economic and aesthetic forces that have shaped the field of chemical synthesis and which have given rise to such concepts as atom-economy [2], step-economy and the ideal synthesis [3]. As reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 378 publications
0
6
0
Order By: Relevance
“…Additional radio continuum data were published by Nestoras et al (2010), Gawronski et al (2010), Pooley (2010), and Bower et al (2010) in Astronomer's Telegrams. Unfortunately, the facilities and frequencies used for these measurements are heterogeneous, so they are difficult to integrate into our VLA light curve and are not used in our analysis (although a spectral index from the Nestoras et al data is listed in Table 2).…”
Section: Observational Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional radio continuum data were published by Nestoras et al (2010), Gawronski et al (2010), Pooley (2010), and Bower et al (2010) in Astronomer's Telegrams. Unfortunately, the facilities and frequencies used for these measurements are heterogeneous, so they are difficult to integrate into our VLA light curve and are not used in our analysis (although a spectral index from the Nestoras et al data is listed in Table 2).…”
Section: Observational Methodsmentioning
confidence: 99%
“…This paper presents complementary radio continuum observations of the 2010 outburst, obtained between 1-45 GHz with the Karl G. Jansky Very Large Array (VLA; Perley et al 2011). Before the 2010 outburst, no radio detections of V407 Cyg had ever been reported (although, see Section 7), but shortly after the nova explosion, V407 Cyg was strongly detected across the centimeter and millimeter bands (Nestoras et al 2010;Gawronski et al 2010;Pooley 2010;Bower et al 2010;Krauss et al 2010). In Section 2, we present our data and describe the radio light curve.…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary studies, a chiral iridium complex modified by ( R )-C3-TUNEPHOS was found to promote the coupling of 1,1-dimethylallene to p -nitrobenzyl alcohol in 55% isolated yield and 76% enantiomeric excess. [17] Erosion of enantiomeric excess is not observed under the coupling conditions, indicating that the product of carbonyl allylation, a secondary alcohol, is not subject to redox equilibration.…”
Section: Hydrogenative Carbonyl Allylation Employing Allenes As Allylmentioning
confidence: 99%
“…A fair amount of extended emission was also present, but impossible to image or model fit reliably with the spatial frequencies available to VLBI. We note that the Allen Telescope Array measured a flux density of 5.8 ± 0.9 mJy at the same frequency just two days earlier [2], clearly indicating that the majority of the flux density at this epoch and frequency is emitted on larger angular scales.…”
Section: Resultsmentioning
confidence: 96%